2020
DOI: 10.9734/jesbs/2020/v33i430216
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceptions on Management of Conflict in Primary Schools in Mberengwa District

Abstract: Introduction: Conflict is major social construct happening in most communities where people of divergent and different backgrounds finds themselves inhabiting a common environment. Schools formulate habitat with semi-seclusion from the rest of society and conflict arising needs to be managed. Also engaging is conflict resolution without taking sides in such environments where children interact with adults more frequently requires skills and training which aspects do not form part of teaching and learning curri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…On the issue of NGOs and the Government make peace with each other for the benefit of the elderly social support, (n = 230; 50%) of the elderly were suggesting that if the NGOs can supply them with the food assistance as they used to do before. This was illustrated by an elderly widow who reported that: The study corroborates some of the social ills pervasive in Mberengwa, like conflicts amongst the schools [48], showing that the elderly are really at the receiving end in a community that exposes them to the vagaries of both nature and human deficiencies and that something drastic needs to be done urgently. The elderly people in the Cheshanga rural area perceive tangible support as the most needed form of social support.…”
Section: Sub-theme: Tensions Between the Government And The Ngosmentioning
confidence: 93%
“…On the issue of NGOs and the Government make peace with each other for the benefit of the elderly social support, (n = 230; 50%) of the elderly were suggesting that if the NGOs can supply them with the food assistance as they used to do before. This was illustrated by an elderly widow who reported that: The study corroborates some of the social ills pervasive in Mberengwa, like conflicts amongst the schools [48], showing that the elderly are really at the receiving end in a community that exposes them to the vagaries of both nature and human deficiencies and that something drastic needs to be done urgently. The elderly people in the Cheshanga rural area perceive tangible support as the most needed form of social support.…”
Section: Sub-theme: Tensions Between the Government And The Ngosmentioning
confidence: 93%
“…The school managers through their experiences are aware that harmonious working relationship, mutual implementation of decisions and peaceful academic environment will be jeopardized, if the school and members of the school community are often in conflict. Nkomo et al (2020), asserted that, conflict creates social change and balance, creates an environment where staff members got to know each other well if controlled within limits and that it assists in the smoothening and running of the institutions. Principals and teachers get to know each other's strengths and weakness through act of conflict as long as it is handled properly.…”
Section: Perception Of Principals and Teachers Of The Impact Of Confl...mentioning
confidence: 99%
“…The current population of Zimbabwe in 2022 is 15,331,428, a 1.59% increase from 2021 with the urban population rising rapidly in tandem with becoming sites of growing inequality between men and women which echoes the inequalities already experienced by women on a daily basis, within their homes and communities in relation to socioeconomic and political participation [4]. Safe shelters and perception by the societies and communities surrounding these have also shown that women and girls are not totally safe from gender based violence (GBV) even with this type of protection [5] and teachers have also intoned on the violence seen in schools among students [6]. Violence in public spaces tends to be acceptable that it is hardly ever talked about.…”
Section: Introductionmentioning
confidence: 99%